Genetic diversity of Xanthomonous citri subsp. citri, causal agent of citrus canker - Arshadi, Farimah (2013)
Asiatic citrus bacterial canker disease is one of the most widespread and economically damaging diseases of citrus, affecting nearly all commercial citrus species and cultivars worldwide and is endemic in Malaysia. It is caused by the bacterium Xanthomonas citri subsp. citri, which causes raised lesions often surrounded by hallow on young leaves, fruits and stems of citrus trees. In this study four states of Peninsular Malaysia were surveyed for occurrence of the disease. Canker was observed in all the states surveyed except Pahang state. Specimens were gathered and 25 strains of the bacterium were isolated. Four different diagnostic tests were used to identify the bacterium, including morphological and biochemical characterization, detached-leaf pathogenicity test, conventional PCR using primer set 2/3 and sequencing. All four methods confirmed the isolates to be Xanthomonas citri subsp. citri. After identification, the isolates were subjected to molecular characterization using rep-PCR primers, ERIC and BOX. After combining the data obtained from each primer pair, similarity coefficients for a pair of isolates were calculated using Dice‟s coefficient index and phylogenetic tree was constructed based on UPGMA clustering method. The mean similarity coefficient for isolates was 73% and our tree clearly grouped isolates according to the geographical location, but not the citrus host they were collected from. The tree was separated into two main clusters at 51% similarity, one including the isolates from Terengganu and the other containing the rest of the isolates from Johor and Selangor. Previous studies show that similarity coefficient less than 70% is associated with different strains or pathovars of a bacterium. This high amount of genetic distance refers to a distinct genetic structure and heterogeneity in populations of Terengganu isolates, while isolates from Johor and Selangor seem to be more genetically uniformed and similar. However, more evidence is required to prove the presence of distinct forms a disease in Malaysia.